Effect of decapitation and exogenous application of gibberellic acid (GA3) and cytokinin (CK) on some physiological characteristics of stevia - Akbari, Mehrangiz; Ghobadi, Mohammad Eghbal; Ghobadi, Mokhtar; Jalali-Honarmand, Said; Saeidi, Mohsen (Cellular and Molecular Biology, 2018)
Stevia (Stevia rebaudiana B.) has auxiliary buds that often remain dormant for a long time and sometimes remain dormant until the plants change at the reproductive stage. This study was designed out to investigate whether decapitation and exogenous application of plant growth regulators enhance the productivity of stevia through breaking the apical dominance and increasing physiological characteristics. Experiment was carried out as a factorial in randomized complete block design with three replications. Factors were consisted two agricultural practices (Decapitation and No-decapitation) and eight foliar spray including without spray as control, water spray, GA3 (300, 600 and 900 µm) and CK (100, 200 and 400 µm). The results of the present investigation indicated a positive response on number of branches and leaves, leaves and stem fresh weight and total dry weight, in both harvests not only from the decapitation of apical buds but also from foliar application of CK (400 µM). Thus, it can be concluded that the decapitation practices in conjunction with foliar application of CK (400 µM) could be used to increase the dry-leaf yield of stevia. However, further studies are required to standardize the dose of CK (400 µM) to improve the yield and quality of stevia.